2000
DOI: 10.1037/0882-7974.15.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of off-target verbosity on communication efficiency in a referential communication task.

Abstract: The referential communication task was used to see if high off-target verbosity (OTV), defined as excessive speech that is lacking in focus, negatively affects communication of nonautobiographical information. The task required 1 individual (the director) to communicate descriptions of abstract figures to another (the matcher). Out of 455 adults aged 63 to 93 who were screened for OTV, 27 directors were drawn from each of the top and bottom 15% of the range of OTV scores and 26 directors and all 80 matchers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 22 publications
3
62
3
Order By: Relevance
“…Individuals who are rated as high in OTV show a consistent pattern of abundant, irrelevant speech that goes far beyond the normal initiation and elaboration of topics found in conversational exchanges. The prevalence of high OTV increases after age 60 years, although a high level of OTV is characteristic of only a small minority of older adults [2]. Psychosocial factors, including greater extraversion and psychosocial stress, are associated with higher levels of OTV, but do not explain the age-associated increase in its prevalence.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Individuals who are rated as high in OTV show a consistent pattern of abundant, irrelevant speech that goes far beyond the normal initiation and elaboration of topics found in conversational exchanges. The prevalence of high OTV increases after age 60 years, although a high level of OTV is characteristic of only a small minority of older adults [2]. Psychosocial factors, including greater extraversion and psychosocial stress, are associated with higher levels of OTV, but do not explain the age-associated increase in its prevalence.…”
Section: Introductionmentioning
confidence: 90%
“…These two measures were combined by principal-components analysis into a single OTV score. Individuals with extreme OTV scores were deliberately oversampled in selecting the phase 2 sample, with approximately one sixth of the 196 phase 2 participants being drawn from each of the highest and lowest 15% of the original distribution and two thirds from the middle 50% [2].…”
Section: Study Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a group ranging in age from 63-95 years, Arbuckle et al (2000) found that the older adults produced more irrelevant personal information than the younger adults in a life-history interview but not in referential communication about tangram figures. In the life-history interview, participants with high verbosity scores made up 5% of the participants from the youngest age group (aged 63-69 years) but 46% of the participants from the oldest group (aged 85-95 years).…”
Section: Ageing and Speech Production 243mentioning
confidence: 99%
“…12 performance, affecting how efficiently the mental lexicon can be searched for words with the appropriate initial letter and how efficiently a text base can be searched for answers to comprehension questions. Those with higher P-Density scores read more rapidly (requiring fewer sec per word) and generated more items meeting the fluency criterion in the available time.Arbuckle, Nohara-LeClair, & Pushkar (2000) have reported that speakers rated high in off-target verbosity also perform poorly on tests of inhibition, including initial letter fluency. They also report that speakers rated high in off-target verbosity use more words and hedges during a referential communication tasks and they refer to such speakers as "inefficient communicators."…”
mentioning
confidence: 99%